INNOVATIVE PEDAGOGICAL STRATEGIES FOR MANAGING LANGUAGE LEARNING ANXIETY IN YOUNG ADULTS (Journal of Science-Innovative Research in Uzbekistan, 2025)
Language learning anxiety is a persistent barrier to effective communication and academic achievement, particularly among young adult learners. This paper investigates innovative pedagogical strategies that can be employed to reduce anxiety in language classrooms. Grounded in affective filter theory and supported by current research, it explores approaches such as gamification, drama-based instruction, project-based learning, mindfulness practices, and digital storytelling. These methods are shown to create engaging, low-stress learning environments that support confidence, risk-taking, and language fluency. The article also discusses the importance of teacher empathy, classroom atmosphere, and learner autonomy in managing anxiety. Overall, the paper argues that a shift toward more creative, student-centered teaching practices can significantly improve language outcomes for anxious learners.